Soundscapes and Brotherhood in the Processions of the Redemption of Captives. The Case of Early-Modern Valencia - Escrivà-Llorca, Ferran (Confraternitas, 2020)
Processions for the redemption of Christian captives held for ransom in the eastern Mediterranean and North Africa were of great importance for the outward expression of Christian faith during the early modern period. The city of Valencia, as a major maritime centre in the Mediterranean, mounted many of these highly symbolic processions during the sixteenth and seventeenth centuries. Two main religious orders were dedicated to freeing captives: the Mercedarians and the Trinitarians. This article considers the soundscape of this type of procession in Valencia at that time, and, in particular, analyzes the major role of confraternities based in the churches of the two orders in the realization of processions. Extant documentation of these two religious houses affords insight into the urban ceremonies occasioned by the redemption processions and offers detailed descriptions of the soundscape they created with the singing of psalms, motets, and the Te Deum laudamus. It also provides an interesting account of the dispute between Trinitarians and Mercedarians over control of ceremonial space in the urban complex—both physical and sonic—occasioned by the processions they organized.